STRATEGI PENGEMBANGAN USAHATANI KOPI ROBUSTA DI KELURAHAN AGUNG LAWANGAN KECAMATAN DEMPO UTARA KOTA PAGAR ALAM - Utami, Ellen Yunia; Batubara, Mustopa Marli (Universitas Muhammadiyah Palembang, 2021)
This research was conducted to knowing how Development Strategy of Robusta Coffee Farming In Agung Lawangan Village Of Dempo Utara Pagar Alam City. This research was conducted in Agung Lawangan Village Of Dempo Utara Pagar Alam City in June to July 2020. The method used is survey. The sampling method used by simple random sampling. Data collection methods used observation and direct interview using aids, a list of question that have been prepared in advance and the data obtained from the relevant institutions that have anything to do with this research. Data processing method used editing, coding, and tabulating, and data analysis used descriptive analysis with a qualitative approach. The result showed that combining of Internal Factor and Eksternal Factor in SWOT Matrix Robusta Coffee Farming In Agung Lawangan Village produce several alternatife strategies that is 1. Increasing the amount of production and quality of robusta coffe anda expanding the marketing network 2. Improve production technology to supply market 3. Strengthen capital for robusta coffee farming and expanding the marketing network 4. Developing robusta coffe, improve the quality robusta coffee through good post harvest 5. Conduct training development of institutional empowerment and farm management, 6.improve the marketing chain robusta coffee with through related institutions 7. Conduct training in robusta coffee cultivation techniques according to recommended techniques and training on how to control pest and diseases.